Religious and Spiritual Diversity in Multiple Modernities: A Decolonial Perspective Focusing on Peripheral Religious Expressions - Parker-Gumucio, C (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This paper challenges the World Religion Paradigm (WRP) dominating religious studies, advocating for a decolonial approach that focuses on diverse and often marginalized religious expressions. The approach that prioritizes world religions over the rich diversity of religious expressions in multiple modernities turns out to be insufficient and biased. Through theoretical research, this paper explores the implications of multiple modernities for the religious landscape. Drawing on Eisenstadt’s theory of multiple modernities, the analysis critiques linear notions of modernization and secularization, and it highlights the complex interplay between religious centers and peripheries. It develops a critical examination of how the theory of the Axial Age, by prioritizing elites and centers in the historical genesis of world religions, generates a preconception that overlooks the religious and spiritual productivity of the peripheries, which persists within current interpretative frameworks. To emphasize the dynamic between center and periphery as a key factor in understanding religious diversity, the text proposes some theoretical theses. By embracing a diversity paradigm and decolonizing frameworks, this paper offers a more inclusive understanding of religious phenomena, contributing to a broader discourse on religion and spirituality beyond Eurocentric perspectives. © 2024 by the author.